Neutrophil-lymphocyte and Platelet-lymphocyte Ratios in Febrile Seizures - Sonay İncesoy Özdemir; Halise Akça; Ayşegül Neşe Çitak Kurt (Galenos Yayinevi, 2022)
Introduction:The neutrophil-lymphocyte ratio (NLR) and the platelet-lymphocyte ratio (PLR) are accepted as the indicators of systemic inflammatory response. The aim of this study was to evaluate the value of the changes in NLR and PLR values as a biomarker in patients presenting with febrile seizure.Methods:Patients with a diagnosis of febrile seizure were retrospectively evaluated. A total of 175 febrile seizure patients and 150 healthy children constituting the control group were included in the study. The febrile seizure type was simple in 113 and complicated in 62 subjects.Results:The NLR value was higher in the febrile seizure group (3.36±3.28) than in the control group (1.82±2.21) with statistical significance (p=0.000). The PLR value was also higher in the febrile seizure group (135.10±80.44) than in the control group (123.43±67.06) but without statistical significance (p>0.05). There was no statistically significant relationship between the NLR or PLR values and age. The main characteristic influencing the NLR and PLR values in the febrile seizure group was found to be the type of febrile seizure.Conclusion:Febrile seizure diagnosis and typing is done clinically, if the examination is performed for any reason, the NLR and PLR values can provide guidance in the differentiation of simple and complex febrile seizures.